Pre-eclampsia affects procalcitonin production in placental tissue. - Agostinis, Chiara; Rami, Damiano; Zacchi, Paola; Bossi, Fleur; Stampalija, Tamara; Mangogna, Alessandro; Amadio, Leonardo; Vidergar, Romana; Vecchi Brumatti, Liza; Ricci, Giuseppe; Celeghini, Claudio; Radillo, Oriano; et al. (Am J Reprod Immunol, 2018)
PROBLEM: Procalcitonin (PCT) is the prohormone of calcitonin which is usually released from neuroendocrine cells of the thyroid gland (parafollicular) and the lungs (K cells). PCT is synthesized by almost all cell types and tissues, including monocytes and parenchymal tissue, upon LPS stimulation. To date, there is no evidence for PCT expression in the placenta both in physiological and pathological conditions. METHOD: Circulating and placental PCT levels were analysed in pre-eclamptic (PE) and control patients. Placental cells and macrophages (PBDM), stimulated with PE sera, were analysed for PCT expression. The effect of anti-TNF-α antibody was analysed. RESULTS: Higher PCT levels were detected in PE sera and in PE placentae compared to healthy women. PE trophoblasts showed increased PCT expression compared to those isolated from healthy placentae. PE sera induced an upregulation of PCT production in macrophages and placental cells. The treatment of PBDM with PE sera in the presence of anti-TNF-α completely abrogated the effect induced by pathologic sera. CONCLUSION: Trophoblast cells are the main producer of PCT in PE placentae. TNF-α, in association with other circulating factors present in PE sera, upregulates PCT production in macrophages and normal placental cells, thus contributing to the observed increased in circulating PCT in PE sera.
Keywords: Adult; Calcitonin; Cohort Studies; Female; Humans; Macrophages; Placenta; Pre-Eclampsia; Pregnancy; Trophoblasts; Tumor Necrosis Factor-alpha; Up-Regulation; Young Adult